Lavoura arcaica: um processo de criação ritualístico-teatral no cinema - Henrique Manoel Silva de Oliveira (2017)
Luiz Fernando Carvalho is a renamed Brazilian movie and television novels and series director. In your first feature film, released in 2001, Lavoura Arcaica, inspired in a namesake romance novel of the writer Raduan Nassar. The director search for originals ways to renew yourself as a creator. Through this research, we have the goal to show a reflection about the creative process from the film director who build a methodology in your movie Lavoura Arcaica with ritualistic structures, looking for lead up all involved at the creative process. Also, we pretended reflect about your laying as a director which deconstructs traditional forms of movie mainstream betting in a production of scene that appear starting from improvisation practices and the relations building between the film participants, the cast, photographer, costumer and the director himself. This reflection was fulllfiled based in director, actors and photographer interview on making off about the film given to six specialists at Ipanema Theater (Rio de Janeiro), 2nd of octuber 2001, transformed in a book: Sobre o Filme Lavoura Arcaica. All materials analyzed in the light of Antonin Artaud texts, quoted by the director on your testimony in the interviews, in special The Theatre and Your Dual, book where Artaud shows your appeals to theatre returns to your ritualistic qualities.